2020
DOI: 10.1038/s41467-020-19843-1
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid protein of SARS-CoV-2 phase separates into RNA-rich polymerase-containing condensates

Abstract: The etiologic agent of the Covid-19 pandemic is the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The viral membrane of SARS-CoV-2 surrounds a helical nucleocapsid in which the viral genome is encapsulated by the nucleocapsid protein. The nucleocapsid protein of SARS-CoV-2 is produced at high levels within infected cells, enhances the efficiency of viral RNA transcription, and is essential for viral replication. Here, we show that RNA induces cooperative liquid–liquid phase separation of the SA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
392
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(454 citation statements)
references
References 40 publications
36
392
0
Order By: Relevance
“…Figure 4A ). N S176D/S188D/S206D displays ~5-fold lower binding affinity to ssRNA compared to N WT binding, a result consistent with previous work examining the impact of LKR phosphorylation on RNA binding(Savastano et al, 2020). We observed a similar trend for the N NTD-LKR construct.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 4A ). N S176D/S188D/S206D displays ~5-fold lower binding affinity to ssRNA compared to N WT binding, a result consistent with previous work examining the impact of LKR phosphorylation on RNA binding(Savastano et al, 2020). We observed a similar trend for the N NTD-LKR construct.…”
Section: Resultssupporting
confidence: 89%
“…N WT p1 contains N-RNA with a loose-coil appearance ( Figure 3B, top left ), similar to that observed for other RNA-bound nucleocapsids (Bharat et al, 2012; Mavrakis et al, 2002). Other recent studies have also observed that N protein undergoes liquidliquid phase separation (LLPS) when mixed with RNA(Carlson et al, 2020; Cubuk et al, 2020; Iserman et al, 2020; Jack et al, 2020; Savastano et al, 2020). In agreement with these results, for N WT p2, we mostly observe spheres corresponding to liquid droplets separated from the surrounding buffer ( Figure 3B, top right ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…S4A; Table S2), notably, we also found that N protein could interact with G3BP1 and G3BP2, the stress granule assembly proteins, which was in line with previous studies 39, 40 . Recent studies found that N protein could impair the stress granule assembly to escape the antiviral effect 40,41 . Thus, reads, remaining Illumina sequence reads were mapped to human (GRCh38) and SARS2 genome by using HISAT2.1.0 with parameters: --rna-strandness RF -dta.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, we also identified numerous host factors associated with N protein ( Fig. S4A; Table S2), notably, we also found that N protein could interact with G3BP1 and G3BP2, the stress granule assembly proteins, which was in line with previous studies 39, 40 . Recent studies found that N protein could impair the stress granule assembly to escape the antiviral effect 40,41 .…”
Section: Discussionsupporting
confidence: 90%